2019
DOI: 10.1002/jcp.29260
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs as potential diagnostic and prognostic biomarkers in gastric cancer: A novel approach to personalized medicine

Abstract: Gastric cancer is the third leading cause of cancer death with 5-year survival rate of about 30-35%. Since early detection is associated with decreased mortality, identification of novel biomarkers for early diagnosis and proper management of patients with the best response to therapy is urgently needed. Long noncoding RNAs (lncRNAs) due to their high specificity, easy accessibility in a noninvasive manner, as well as their aberrant expression under different pathological and physiological conditions, have rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 148 publications
(115 reference statements)
0
66
0
Order By: Relevance
“…Increasing studies suggest that abnormal expression of lncRNAs is closely related to the occurrence of various human diseases, especially tumorigenesis and cancer progression 9,26,27 . Many studies have found that lncRNAs are involved in some tumor pathological processes and play an important role in gastric tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies suggest that abnormal expression of lncRNAs is closely related to the occurrence of various human diseases, especially tumorigenesis and cancer progression 9,26,27 . Many studies have found that lncRNAs are involved in some tumor pathological processes and play an important role in gastric tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of attention is being recently paid to the expression profiles and roles of lncRNAs in carcinogenesis and cancer progression. [28][29][30] An increasing number of studies suggest that the alteration of lncRNA expression is closely linked to the onset and progression of OS. [31][32][33] Therefore, an investigation of specific molecules that are dysregulated in OS may reveal potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Despite the progresses in detection methods, surgical technology, and medicine therapies in these years and the 5-year survival rate of early gastric cancer can reach >90%, most patients present with advanced-stage gastric cancer, which limited treatment options, and the global 5-year survival rate is 5%-10% in advanced stages. [3][4][5][6][7] Thus, the management of gastric cancer is challenging. Identifying convincing biomarkers for prognosis may offer insights into prognostication and contribute to development of individualized treatment strategies in gastric cancer patients.…”
Section: Introductionmentioning
confidence: 99%